APLIKASI MANAJEMEN LABORATORIUM KOMPUTER TEKNIK INFORMATIKA UIN ALAUDDIN MAKASSAR - Yusran Bobihu (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
As a central lab where students majoring in Computer Science, informatics engineering laboratory manager often face problems in conducting lab. Problems faced by students who do not like the discipline in following lab and lab equipment often lost in the computer lab. Based on these problems, the aim of this study is to minimize the preparation of the case - that by restricting access rights of students who get into the computer lab informatics techniques. To achieve that goal, then do step - a step which consists of type of research, system design, implementation and testing of the system. The type of study is a quantitative descriptive research research that systematically describes the condition of the fact of the object of study, while the design of systems using Delphi programming language with database DbIsam. The testing method using Blackbox method that focuses on the functional requirements of the software. With the application to be built, then the lab manager can more easily monitor and supervise lab activities. Attendance Laboratory, Asiten and in monitoring student may at any time by the Head of the Computer Laboratory.